Can the Dividend Payout Ratio Mediate the Relationship Between the Current Ratio, Debt-to-Equity Ratio, and Stock Price? - Samsuri, Samsuri; Zamasari, Abdullah; Andari, Titiek Tjahja (E-Jurnal Akuntansi, 2024)
This study examines the influence of the current ratio and debt-to-equity ratio on stock prices, with the dividend payout ratio as a mediating variable, focusing on companies listed in the LQ45 index on the Indonesia Stock Exchange. The research population comprised 64 companies, with a sample of 28 firms selected through purposive sampling. Path analysis and the Sobel Test were employed to evaluate the mediating effect of the dividend payout ratio. The results indicate that while the current ratio does not affect the dividend payout ratio, it has a significant positive impact on stock prices. Conversely, the debt-to-equity ratio exerts a significant negative influence on both the dividend payout ratio and stock prices. Moreover, the dividend payout ratio shows no significant effect on stock prices and does not mediate the relationship between the current ratio, debt-to-equity ratio, and stock prices for LQ45 companies during the 2019–2023 period. Keywords: Current Ratio; Debt to Equity Ratio; Dividend Payout Ratio; Stock Price.